Direct determination of absolute configuration: a vibrational circular dichroism study on dimethyl-substituted phenyloxiranes synthesized by Shi epoxidation - Fristrup, P.; Lassen, P.; Tanner, D.; Jalkanen, Karl (Springer Berlin, 2008)
The three possible dimethylsubstituted phenyloxiranes (cis, trans and geminal) were synthesized in both racemic (mCPBA) and enantiomerically enriched forms (Shi epoxidation) and subjected to a vibrational circular dichroism study. The experimental spectra were compared to theoretical spectra obtained using DFT/B3LYP calculations, and the differences between experiment and theory are discussed. The absolute configuration at the benzylic position was established as being (R), (S) and (R) for the cis, trans and geminal dimethylsubstituted phenyloxiranes, respectively. In all three cases the configuration of the major enantiomer was in accordance with a simple transition state model based on the spiro reaction mode.